PENINGKATAN KAPASITAS PENGELOLAAN LIMBAH MEDIS FASILITAS PELAYANAN KESEHATAN DI GROGOL PETAMBURAN JAKARTA BARAT - Pou, Rudy; Tarigan, Gita Handayani; Purwaningrum, Pramiati; Jodie, Himawan; Eskar, Yefy (Jurnal Abdi Insani, 2024)
Medical waste gives a serious threat to environmental health and requires special handling and management. The problem is growing with the increasing number of health care facilities. Health workers must have good knowledge and attitudes about medical waste management. The target of this community service is given to medical waste managers in each health care facility. With the training provided, it is hoped that knowledge and practice regarding medical waste management will increase. The training participants are the owners or heads of clinics or those in charge of installations for maintaining hospital infrastructure in the Grogol Petamburan sub-district area, West Jakarta. The number of training participants was 33 representatives (43%), who came from all health care facilities in the Grogol Petamburan area. One third (33%) of health workers were not trained / exposed to medical waste management, even though a decree on medical waste management (82%) had been issued along with technical guidelines (82%) and standard operational procedures (88%). The practice of sorting waste is carried out by almost all health facilities (94%), 73% of health facilities record the amount of medical waste production in their daily logbook, medical waste processing uses third party services (100%), more than half (52%) of cleaning staff and medical staff have never attended medical waste management training and only a few cleaning staff do not use PPE when managing medical waste (6%). Many janitors or employees have never received training regarding medical waste management. Continuous outreach efforts are needed by interested parties to achieve standardized medical waste management in every health care facility. It is necessary to strictly implement medical waste management rules, health care facilities are required to train their health workers. Training and retraining regarding medical waste must be planned and implemented.